Working at Ford: The Asian Women's Story (2007)
2007 "Working at Ford: The Asian Women's Story", 2007, Boston, Sarah Read the Notes by Adina Batnitzky (below) to learn more about the background to the film. Click on the video icon to watch the film or click on the PDF icon to read a transcript.